(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
Fossil fuel has been an energy source for decades which has been causing large emissions of CO2 and consequently has negatively influenced the climate of earth. For this reason, there has been large demand for new resources of energy that are eco-friendly for the environment. Exchange the energy sources needs engineering materials that have ability to convert the energy from one image to another. Oxide glasses are considered inorganic materials. They gain an interest for wide range of engineering applications of energy like in solar panels because They appear strength and good resistance for environmental conditions; in addition to good thermal stability and feasibility of shaping and processing. However, there still are challenges of implementing glass in energy applications. This short review will highlight the main challenges of oxide glasses and will present some ideas for them.